ON THE ROLE OF INTRAUTERINE INFECTIONS IN THE DEVELOPMENT OF CHILDREN'S HEALTH AT THE REGIONAL LEVEL (ON THE EXAMPLE OF NORTH CAUCASIAN FEDERAL DISTRICT) - Igor Nikolaevich Bobrovsky; Diana Mihailovna Dementieva; Elena Mihailovna Kasparova; Valeria Nikolaevna Orobinskaya; Anatoliy Nikolaevich Goryachev (Современная наука и инновации, 2022)
The article highlights the issues of the statistical research the health of children and adolescents with congenital malformations (compared to similar all-Russian indices). The effect of intrauterine infection, causing a violation of ontogenesis and formation of pathologies of the musculoskeletal system, malformations of the cardiovascular and urogenital system.